Rice straw mulch and organic amendment effects on yield and yield components of dry direct seeded Boro rice - Rahman, M M; Hossain, B; Jahangir, M M R (SAARC Journal of Agriculture, 2023)
An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, during January to June 2019 to find out the effect of rice straw mulch and organic amendments on yield and yield attributes of Boro rice under dry direct seeded system. The experiment comprised two sets of treatments viz., (a) Mulch: (i) Rice straw mulch (M1) and (ii) no mulch (M2) and (b) organic amendments : (i) Control (Recommended Doses of Fertilizers, RDF) (T1), (ii) RDF + Farm Yard Manure, FYM (T2); (iii) RDF + Mustard Oil Cake, MOC (T3); (iv) RDF + FYM + Trico-compost (T4); (v) RDF + Trico-compost + MOC (T5); (vi) RDF + FYM + MOC (T6) and (vii) RDF + Trico-compost (T7) in a split-plot design with three replications. The results showed that rice straw mulch did not have significant effect on yield and yield attributes of rice. The interaction between rice straw mulch and organic amendment was not significant for grain yield and any other characters. Based on the study results it is concluded that maximum yield of BRRI dhan28 in Boro season under dry direct seeded system could be achieved through organic amendment with Mustard Oil Cake @ 0.5 tha-1 or Farm Yard Manure @ 5 tha-1 + Trico-compost @ 3 tha-1 or Trico-compost (TC) @ 3 tha-1 in addition to the application of recommended doses of fertilizers (RDF). SAARC J. Agric., 21(1): 103-113 (2023)